2018
DOI: 10.1111/ejn.14069
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of sensorimotor transformation and action selection

Abstract: Ray Guillery made major contributions to our understanding of the development and function of the brain. One of his principal conceptual insights, developed together with Murray Sherman [S.M. Sherman & R.W. Guillery (2001) Exploring the Thalamus. Elsevier, Amstrerdam; S. Sherman & R. Guillery (2006) Exploring the Thalamus and Its Role in Cortical Functioning. Academic Press, New York, NY; S.M. Sherman & R.W. Guillery (2013) Functional Connections of Cortical Areas: A New View from the Thalamus. MIT Press, Camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 94 publications
(115 reference statements)
1
17
0
Order By: Relevance
“…We report here that, in addition to the hippocampus, CB recruit a sensorimotor network when learning the detection task. Our results fit remarkably well with recent literature on visually guided behavioral learning [42][43][44][45] , and spatial learning [46][47][48] . It is well known that brain volume can be associated with learning behavior 49,50 .…”
Section: Brain Volumes and Learning Rate Of Detection Correlationssupporting
confidence: 91%
See 1 more Smart Citation
“…We report here that, in addition to the hippocampus, CB recruit a sensorimotor network when learning the detection task. Our results fit remarkably well with recent literature on visually guided behavioral learning [42][43][44][45] , and spatial learning [46][47][48] . It is well known that brain volume can be associated with learning behavior 49,50 .…”
Section: Brain Volumes and Learning Rate Of Detection Correlationssupporting
confidence: 91%
“…Furthermore, several recent studies have linked hippocampal volumetric differences in healthy 47 , and clinical populations with the ability to learn 49 . A recent study also demonstrated traces of learning in thalamo-cortical circuits 42 , and the impact of sensorimotor networks in guiding learning behavior 44 .…”
Section: Brain Volumes and Learning Rate Of Detection Correlationsmentioning
confidence: 91%
“…Elevated arousal threshold is a core feature of sleep 61 and the mechanisms that allow flexible arousability are likely conserved. In mammals, the flow of sensory information is thought to be gated by the thalamus 57,62 but olfactory information can be modulated despite not passing through this brain region 63 . This suggests that different sensory modalities can be regulated independently, a view supported by our results.…”
Section: Peptones Are Made By Partial Hydrolysis Of Dietary Proteins mentioning
confidence: 99%
“…3 years may acquire more information 3 ) . As sensory and motor signals are inextricably linked 34) , gross motor ability is related to oral sensory processing. Thus, oral sensory processing could be an indicator of gross motor abilities.…”
Section: Discussionmentioning
confidence: 99%